THE INFLUENCE OF THE WORK ENVIRONMENT AND INDIVIDUAL CHARACTERISTICS ON EMPLOYEES’ JOB SATISFACTION - Agus Susanto; Hengky Kosasih; Tina Linda; Ika Puspa Satrianny; Thamrin Thamrin (Sekolah Tinggi Pariwisata Mataram, 2022)
This research investigates the influence of the work enviroment and individual characteritis on employees job satisfaction. This skripsi contributes to the working environment and employees’ individual characteristic to increase employees job satisfaction. In carrying out the work or character of an individual must be able to put themselves and their work environment so well that it will affect the individual can achieve the expected job satisfaction. In the world of work, usually relate to a person's attitude to his work. Linkage attitude with this work will pave the way positive or negative evaluative held by employees about aspects of their work environment. This means that every person on the job reflects the experience pleasant and unpleasant in his work and hopes for the future. The working environment is meant here is the physical work environment and non-physical, such as acceptable behavior management and workplace environment itself (workplace), among others working facilities and security. If the work environment possible, then the employees will make the workplace a fun in performing activities works, so as to reduce fatigue, which in turn can lead to satisfaction with the job. As such, working environment and individual characteritic relationship does have the potential to create an employes job satisfaction.